Spin-triplet transitions in (γ,p) and (γ,n) reactions of two-body ⁴He disintegration by photons of energies below 80 MeV - Lyakhno, Yu.P.; Gorbenko, E.S.; Dogyust, I.V. (Вопросы атомной науки и техники, 2002)
The simultaneous least-square fit of expressions for differential cross-sections and asymmetry to the experimental data on dσ/dΩ and Σ(θ), obtained at NSC KIPT, was realized. A set of three bilinear equations with three unknown amplitude modules | ³P₁ | E1, | ³S₁ | M1 and | ³D₁ | M1 was derived; preliminary data about the magnitudes of these amplitude modules were obtained. It is shown that the ³D₁ М1 amplitude is the highest in magnitude.